10th International Conference on Developmental Coordination Disorder - Comportamento Motor, Sociedade Brasileira de (2013)
10th International Conference on Developmental Coordination DisorderJune 28 - July 1, 2013Escola de Educação Física Fisioterapia e Terapia OcupacionalUniversidade Federal de Minas Gerais Conference Book